Synergistic Effect of Antifungal Activity of Medicinal Plants with Transition Metal Ferrocyanides Against Rhizoctonia solani - Bharti, Dipti; Arora, Charu; Gupta, Suman (Asian Journal of Chemistry, 2012)
Manganese, cobalt, nickel, copper, zinc and cadmium ferrocyanides were synthesized and characterized by IR spectra, magnetic susceptibility and elemental analysis studies. The natural antifungal plants such as Acacia nilotica, Emblica officinalis, Nerium oleander and Withania somnifera were showed synergistic effect with transition metal ferrocyanides. The natural antifungal plant extracts with metal ferrocyanides complexes were found to be having more antifungal property in comparison to metal ferrocyanides and plants extract alone. Antifungal activities of natural antifungals, metal hexacyanoferrate(II) compounds were tested against Rhizoctonia solani causing black scurf in potato. Cadmium ferrocyanide with Withania somnifera extract and nickel ferrocyanide with Acacia nilotica extract complexes were found to have maximum and minimum antifungal properties respectively.